2004
DOI: 10.1063/1.1739231
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reaction-driven tip-streaming phenomena in a pendant drop

Abstract: We describe a chemical oscillatory phenomenon which occurs as follows: a pendant drop of water is immersed in a viscous oil, both phases containing reagents which react to produce a surfactant at the interface. As the drop falls away from the tip of a small needle, the remaining interface spontaneously elongates into a sharp cone and ejects small droplets from the pointed tip. The tip then either contracts and re-elongates periodically, or remains steadily elongated. Small droplets continue to be ejected in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 23 publications
5
40
0
Order By: Relevance
“…2(a), self-driven Marangoni singularities have not been thoroughly studied. Marangoni-driven flows exhibiting interfacial singularities, which motivated the present study, were found experimentally only recently [19,[36][37][38][39] and are shown in Figs. 2(b) and 2(c).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…2(a), self-driven Marangoni singularities have not been thoroughly studied. Marangoni-driven flows exhibiting interfacial singularities, which motivated the present study, were found experimentally only recently [19,[36][37][38][39] and are shown in Figs. 2(b) and 2(c).…”
supporting
confidence: 64%
“…(7) Let us identify the conditions under which a solution local near a cusp singularity exists in the Stokes approximation. The corresponding stream function (6) satisfies the kinematic boundary condition (3) provided [17,35] -viscous stresses in the surrounding phase deform the drop, which forms pointed ends; (b) chemical reaction-driven tip streaming [19,36,37] -the acid-base chemical reaction at the water-oil interface produces a surfactant, which drives the Marangoni flow along the interface leading to a conical shape of the drop with a singular cone tip', (c) surfactant-driven fingering [38,39]-soapy water displaces air in the narrow space between two glass plates (Hele-Shaw cell) and eventually leads to fingering with cusps between the fingers. 043019-2 CUSPS AND CUSPIDAL EDGES AT FLUID INTERFACES: ... which allows us to rewrite the formula (6) as…”
mentioning
confidence: 99%
“…Our thread formation and tipstreaming observations also closely resemble recent work in which tipstreaming was observed as a result of a chemical reaction that produces surfactant at an oil-water interface. 48 During pendant drop measurements of the dynamic surface tension, the authors observed that on occasions in which the pendant drop breaks off and settles in the outer liquid bath, this pinchoff is followed by tipstreaming of tiny droplets, in this case ϳ4 micrometers, for a sustained period of time. The authors offer physical arguments that this process results from strong surface tension gradients and they show that an apparent capillary number for the process is approximately Ca Ϸ 0.5 as is expected for classic tipstreaming.…”
Section: -9mentioning
confidence: 99%
“…In this context, the peculiar observation of the spontaneous motion of a water-alkali pendant drop at the tip of a capillary in the oil-acid environment reported by Fernandez and Homsy 15 (FH) was a promising finding, cf. Figure 1, named chemical reaction-driven tip-streaming (CRDTS).…”
Section: A Chemical-reaction Driven Tip-streamingmentioning
confidence: 98%